Cellulose from bacteria as a delivery system for improved treatment of infectious diseases: A review of updates and prospects - Roque-Borda, Cesar Augusto; Carnero Canales, Christian S. [UNESP]; Primo, Laura Maria Duran Gleriani [UNESP]; Colturato, Vitória Maria Medalha; Polinário, Giulia [UNESP]; Di Filippo, Leonardo Delello [UNESP]; Duarte, Jonatas L. [UNESP]; Chorilli, Marlus [UNESP]; da Silva Barud, Hernane; Pavan, Fernando R. [UNESP] (Elsevier, 2024)
Cellulose from bacteria is a high-purity biomaterial naturally produced by bacteria as part of their metabolic process. Although it inherently lacks antimicrobial activity, its modification with bioactive substances can significantly enhance its efficacy beyond that of the original compounds. This biomaterial features a unique ability to retain substantial quantities of liquids within its three-dimensional network, making it a prime candidate for biomedical applications. Versatile in its properties, it can be utilized across various industries. Previous research has highlighted its capacity to exhibit antimicrobial properties and to encapsulate nanostructured materials, thereby augmenting its antibacterial effectiveness. This review focuses on the use of cellulose from bacteria as a carrier for active compounds, specifically targeting antibacterial activity against drug-resistant strains. We explore its role in innovative bacterial cellulose-based systems, which present a promising solution for tackling bacterial resistance. This review aims to showcase the potential of bacterial cellulose in developing new devices and treatment strategies that address critical concerns in global health.
Keywords: Bacterial cellulose; Nanocarriers; Nanocomposites; Nanoparticles